Isolation, identification, and characterization of plant growth-promoting bacteria from Pisha sandstone for application as a microbial inoculant in soil rehabilitation - Fang, Xiuwen; Gao, Haiying; Liang, Zhishui (Frontiers in Microbiology, 2025)
Pisha sandstone is a loosely cemented sedimentary rock widely distributed in the Yellow River Basin and the Ordos Plateau. Due to its high montmorillonite content (20–30%) and low quartz content (approximately 50%), it rapidly disintegrates upon water exposure, resulting in severe soil erosion and contributing to the major coarse sediment in the mid-upper reaches of the Yellow River. Additionally, its low mechanical strength and poor fertility limit the effectiveness of traditional conservation approaches. In this study, an eco-friendly plant-microbe strategy for restoring degraded Pisha sandstone areas was proposed. Plant growth-promoting bacteria were isolated from the rhizosphere of Medicago sativa and reclaimed coal-mining lands in different Pisha sandstone areas. Of 97 isolates, five bacterial strains (F11, F6, G1, G3, P9) demonstrated significant activity in phosphate solubilization, nitrogen fixation, indole-3-acetic acid (IAA) biosynthesis, and siderophore production. They were identified as Klebsiella, Acinetobacter, Herbaspirillum, Pseudomonas, and Serratia. Pot experiments using Medicago sativa and Astragalus adsurgens in Pisha sandstone substrates revealed that bacterial inoculation significantly improved soil organic matter, available nitrogen, phosphorus, and potassium, and enhanced plant height and biomass production. The microbial agent formulated with strains F11 and G1 (MI3) exhibited the optimal performance. These results highlight the potential of plant-microbe interactions for ecological restoration of fragile sandstone ecosystems and offer a sustainable strategy for controlling soil degradation in the Yellow River Basin.